Effect Of Slab Thickness On Weld Distortion Results In Medium Carbon Steel AISI 1045 By SMAW Method - Aulia, Irsyad Haryono; Tarkono, .; Zulhanif, . (Jurnal Ilmiah Teknik Mesin FEMA, 2013)
This research aimed to investigate the effect of width plate variation to distortion caused by welding in AISI 1045 light steel alloy plate. This kinds of steel is formable by heat treatment and often for making mechanical component use. Sometimes repairing mechanical component was done by welding. The deformation that occurred by welding are caused by distortion. Distortion is shape transformation proccess of welding result which caused by unbalance between expanding metal while heating and shrink while colding.This research takes places in Bureau of Work and Training (BLK) Bandar Lampung, for making the test specimen and distortion measurement, while the hardness test and microstructure test held in Material Laboratory Lampung University. Before testing the specimen, first of all the steel must be welded well, using Shielded Metal Arc Welding (SMAW) method. The electrode which used for welding is E 6013 RB 26, while the joint are V form with 80 A electric current. The welding region that will be the sample data test are base metal, HAZ, and weld metal for hardness test and microstructure test. The variation of plate width are 2, 5, 8 mm.From the result of testing materials, we can make some conclution which is, the largest distortion level experienced by plate occurred in 8 mm width of plate, while  the largest hardness number experienced by plate occurred in base metal region with 57,5 HRC number. Although, the 8 mm width of plate is the most thick of all specimen, the hardness number in HAZ refgion has the smallest number of hardness. Keywords: distortion, plate, light steel, SMAW